Influence of the deposition parameters on the growth of SiGe nanocrystals embedded in Al2O3 matrix - Vieira, E. M. F. (2011)
Si1-xGex nanocrystals (NCs), embedded in Al2O3 matrix, were fabricated on Si (100) substrates by RF magnetron sputtering technique with following annealing procedure at 800 C, in nitrogen atmosphere. The presence of Si1-xGex NCs was confirmed by grazing incidence X-ray diffraction (GIXRD), grazing incidence small angle X-ray scattering (GISAXS) and Raman spectroscopy. The influence of the growth conditions on the structural properties and composition of Si1-xGex NCs inside the alumina matrix was analyzed. Optimal conditions to grow Si1-xGex (x~0.8) NCs sized between 3 and 4 nm in Al2O3 matrix were established.